Rapamycin inhibits FBXW7 loss-induced epithelial-mesenchymal transition and cancer stem cell-like characteristics in colorectal cancer cells - Wang, Yuli (2013)
Increased cell migration and invasion lead to cancer metastasis and are crucial to cancer prognosis. In this study, we explore whether FBXW7 plays any role in metastatic process. We show that depletion of FBXW7 induces epithelial-mesenchymal transition (EMT) in human colon cancer cells along with the increase in cell migration and invasion. Moreover, FBXW7 deficiency promotes the generation of colon cancer stem-like cells in tumor-sphere culture. mTOR inhibition by rapamycin suppresses FBXW7 loss-driven EMT, invasion and stemness. Our results define the FBXW7/mTOR axis as a novel EMT pathway that mediates cancer invasion.